HUKUMAN HAD BAGI PELAKU HOMOSEKSUAL PERSPEKTIF MUHAMMAD ABDUH - Alwin, Muhammad (LEGALITE, 2018)
Islamic jurisprudence see that sexual desire is a humanbase, a natural power that is in a human. So, islamicjurisprudence regulate a human biological sexual desire channelby a marriage, and they don?t agree a sexual deviation, such ashomosexual. Homosexual is a bad behaviour that is prohibitedin islamic jurisprudence based on al-Quran and hadis. Scribes ofislamic jurisprudence agree to forbid homosexual, although there are so many opinion about law sanction for them. Some of thescribes say that they have to be killed, have to be punished, suchas a judgement for they commit an adultery, and even they say that homosexual will be punished in jail.